Milling of Inconel 718 block supports fabricated using laser powder bed fusion. (August 2018) - Tripathi, Varad; Armstrong, Andrew; Gong, Xi; Manogharan, Guha; Simpson, Timothy; De Meter, Edward
Abstract: There is significant interest in using laser powder bed fusion (L-PBF) to print metallic parts from super-alloys such as Inconel 718. L-PBF frequently requires the printing of support structures for overhanging regions of the solid part in order to mitigate warping and distortion. After the part is printed, machining processes are often employed to remove the supports from the solid part. Surprisingly, little is known regarding the machining behavior and machinability of these support structures. In this study, the milling behavior of Inconel 718 block type supports was investigated. Standard block supports of varying height were fabricated and peripherally end milled to study deformation and fracture behavior, specific cutting energy, the influence of tooth-support wall interactions on milling forces, and tool wear. The investigation revealed that supports do not uproot from the base or generally collapse when milled. Instead, they maintain their structure and support localized chip formation, despite the fact that they are designed to break away from the base using hand tools. The specific cutting energy of milling blocks supports is 12% of that of full density metal when considered on a swept volume basis. If metal volume removal is considered, the density normalized specific cutting energy is 43% of that of full density metal. Water fall FFT analysis of the forces measured during the milling of block supports revealed stronger relative contributions at higher frequencies and greater time sensitivity than the forces measured during the milling of full density metal. These are due to tooth-support wall interactions. Finally a preliminary tool wear study showed that a TiAlN coated carbide end mill is more prone to pre-mature failure when machining block supports than fully dense metal. This failure is due to fracture at the corner radius, and is possibly due to tooth-support wall interactions.